Measurement of flourishing: a scoping review - Rule, Andrew; Abbey, Cody; Wang, Huan; Rozelle, Scott; Singh, Manpreet K. (Frontiers in Psychology, 2024)
Flourishing is an evolving wellbeing construct and outcome of interest across the social and biological sciences. Despite some conceptual advancements, there remains limited consensus on how to measure flourishing, as well as how to distinguish it from closely related wellbeing constructs, such as thriving and life satisfaction. This paper aims to provide an overview and comparison of the diverse scales that have been developed to measure flourishing among adolescent and adult populations to provide recommendations for future studies seeking to use flourishing as an outcome in social and biological research. We find that most common scales used to measure flourishing are multi-dimensional and assess features over monthly or yearly intervals, and many have been translated and validated across multiple geographical contexts, including higher- and lower-income countries. Complementing self-report measures with other social, economic, regional, and biological indicators of flourishing may provide a holistic and widely applicable measure of wellbeing that could guide strategies to sustain flourishing societies.